Using a Smartphone to Assist in Physical Therapy - Thepjit Cheypoca; Kongsak Anuntahirunrat (My University, 2021)
In this paper, the use of accelerometer, gyroscope, magnetometer and GPS. A basic sensors available on smartphones, in the treatment of paresis symptoms, patients as a way of encouraging physical therapy on their own without having to travel to the hospital. And it is a burden to doctors and physiotherapists, making it possible to serve a large number of patients will explored. It also provides therapeutic information to improve individual physical activity. A smartphone that attached to the patient at a given location.It sends values from sensors to databases in the cloud. The data provided by the database will analyze and diagnosed by doctors and physiotherapists.
Keywords: Mobile Health and mHealth Applications